The Bloomsbury handbook of the anthropology of sound - Schulze, Holger (New York Bloomsbury Academic, 2021)
An authoritative collection of research covering ethnographic field research and cultural history that explores our experience with sound in our everyday lives"--
Introduction : what is an anthropology of sound? -- Living with sonic artifacts -- Sound flesh -- The habitat in sound -- Sonic desires -- The listening machines -- Sensologies.
includes bibliographical references (pages 487-535), discography (536-540), and index.
Keywords: Music -- Social aspects; Sound -- Social aspects